Biomechanical study of cross-country skiing - Lund, M. (2005)
This investigation is a biomechanical study of how the stiffness in pectoralis major (the big chest muscle) affects the muscles in the upper back during the fourth gear in Cross-country skiing free-style technique. It is believed that cross-country skiers often have a stiff pectoralis major, which may result in an increased work for the poling. Further, a stiff pectoralis major will limit the range of motion for the backward pendulum (extension) of the arm, important in the fourth skiing gear. The question to be answered in this report is what a person with a stiff pectoralis major can do to be able to use the same technique as one with a normal pectoralis major. Should stiffness in pectoralis major be decreased and/or should the upper back muscle forces be increased, how much and which ones. The investigation was performed in the inverse dynamics software The AnyBody Modelling System. In inverse dynamics the movement is the input and the program calculates the muscle forces for output. First the resting length for pectoralis major was measured. This was needed for individual calibration of the stiffness for this muscle. The motion of a skier was calculated from a visualisation produced after a recording by a motion capture system (3-D video recording). Thereafter several pectoralis major tendon lengths were tested for the skiing motion with the AnyBody Modelling System. The pole forces and the mass of the poles were not included in the skiing model. From the motion recording it was not possible to calculate the motion of the shoulder; therefore the shoulder was held fix in this investigation. Since it is not known how to decrease the stiffness in a muscle the muscles in the upper back (antagonists to pectoralis major) have to increase their forces to balance the motion. The results of this investigation showed that forces of the outward rotators of the arm, the adductors of scapula and the basin parts of latissimus dorsi have to be increased equally to balance the motion. Stretching should be used to increase or maintain the range of motion for pectoralis major. If the movement of the shoulder had been included in the model the results would probably have been different.